Airborne infection control practices in homes for the aged in the context of tuberculosis elimination - Zinia T Nujum; S Sindhu; P S Rakesh; G Remya; U Anuja (Wolters Kluwer Medknow Publications, 2023)
Background: National Strategic Plan to End tuberculosis (TB) in India 2020-2025 aims to prevent the emergence of TB in susceptible populations. Airborne infection control (AIC) practices in high-risk settings like homes for the aged (HFA) will be essential to achieve this. Objective: The objective is to assess the AIC practices (AICPs) in HFA in the Kollam district in Kerala, India. Materials and Methods: A mixed method approach was used. the study was done in five HFA s in a southern district of Kerala to find AICPs. Using purposive sampling, in-depth interviews was conducted among inmates with recent respiratory infection and administrators. Environmental measures were assessed using an observation checklist. Results: Ventilation was inadequate in 25%-40% of HFA. Air change per hour and distance between beds were less. Very few inmates were aware of the need for proper ventilation and personal hygiene. Wearing masks and hand hygiene was not practiced. Administrators faced shortages of space, funds, and human resources for caring for hospitalized inmates, and psychiatric and terminally ill patients. Conclusions: There is a need to train the staff and inmates on AIC. Infrastructural improvements, like the use of partition screens in the short term and the creation of model airborne infection control HFA in the long run, with a collaborative effort from health professionals and architects, are needed for TB elimination efforts to succeed.